Predictors of youth voluntary participation in urban agriculture programme in Malaysia: a review - Tiraieyari, Neda; Hamzah, Azimi (Canadian Center of Science and Education, 2015)
Urban agriculture (UA) has drawn the attention of Malaysian policy makers. University Putra Malaysia (UPM) has taken the lead in introducing programmes to urban residents. The university’s strategy is to train student volunteers to play the role of change agents serving urban residents to implement the programme. UPM programme planners need to build a large population of long-term students who voluntarily participate in the programme. Hence the university, specifically the faculty of agriculture, is meeting the challenge to produce candidates prepared with the knowledge, skills, and disposition to participate voluntarily in the UA programme. This paper reviews the existing literature on factors to predict voluntary participation among young students. The authors propose a conceptual model for programme developers to promote youth participation in a voluntary programme. Research is recommended to predict factors influencing UPM students’ voluntary participation in the UA programme. Further research is also recommended to explore how programme planners can overcome potential barriers to students’ participation in the programme. These investigations could help stakeholders design a programme that appeals to more students and urban residents.